Peran Entrepreneurial Marketing dalam Peningkatan Kinerja Pemasaran pada Industri Rumahan Kabupaten Kendal, Jawa Tengah - Bibi Arfanly; Ma'mun Sarma; Muhammad Syamsun (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2016)
As a part of Micro Small Medium Enterprises, home industry plays a very important role as new jobs provider that is expected to decrease unemployment and distribute wealth among society. Home industry development needs to be done in Kendal Regency. However in its implementation, this home industry faces many problems, one of them is marketing. It shows that there needs to be right marketing method and strategy to develop home industries. One of the approaches that is used right now by Small Medium Enterprises is entrepreneurial marketing. This research aims to (1) analyze the achievement being practiced by home industry in Kendal, (2) analyze the impact entrepreneurial marketing has towards the marketing performance of Kendal’s home industry. Respondents in this research are 67 home industry entrepreneur in Kaliwangu district and Patebon district, Kendal Regency. Sampling method uses non probability sampling method with convenience sampling technique. The data was analyzed with transformation index analysis and structural equation modeling with partial least square approach (SEM PLS). The result of the research shows that the implementation of entrepreneurial marketing has been quite good and the biggest aspect of entrepreneurial marketing is shown by strategic ability. According to SEM PLS analysis, concept, strategy, and market intelligence variables on entrepreneurial marketing are significant to marketing performance.